Origin of hysteresis in the transfer characteristic of carbon nanotube field effect transistor - Ong, Hock Guan (2013)
Using electrostatic force microscopy, we show direct evidence of charge injection at the carbon nanotube–SiO2 interface leading to the appearance of hysteresis. The dynamic screening effect of the injected charges is revealed step by step. Further temperature dependent tests also demonstrate the effect of SiO2 surface chemistry. Furthermore, we conclude that it is not practical to use such a device for memory application because of data retention and storage density issues.